What contributes to the government-citizen knowledge sharing: Analysis of 293 cities in China - Huajun Sun; Liping Fu; Shu Yang (Journal of Innovation & Knowledge (JIK), 2023)
Advocacy for knowledge sharing (KS) is increasing as it can improve novelty and agility in policy development and service delivery. To determine the combination of factors that best contributes to high-quality government-citizen KS, this study adopts necessary condition analysis (NCA) and a fuzzy-set qualitative comparative analysis (fsQCA). Three primary findings are supported. Cities with higher economic development achieve superior KS by enhancing citizens' motivation to participate; traditional cities that are in transition succeed in KS by leveraging the established strength of the local government; in contrast, less developed cities succeed in KS based on central government guidance. These findings highlight the significance of comparing multi-factor configurations across scenarios. They can be utilised to discover suitable solutions for government-citizen KS in different cities.
Keywords: 650; Fuzzy-set qualitative comparative analysis' necessary condition analysis; Government-citizens; Knowledge sharing